Ship to shore art and the lure of the sea - Wainwright, Jean; Hoare, Philip 1958- (John Hansard Gallery, 2018)
Ship to Shore was an exhibition that featured painting, film, photography, sculpture and prints that evoked the vastness of oceans, the romance of sea travel and ship-to-shore communications. The exhibition was shown across two venues in Southampton. The works by contemporary artists were juxtaposed with voice recordings from Southampton's past, beautiful historic paintings, maritime instruments, posters, postcards, cruise ship memorabilia and other archival objects from the city's rich collections. This publication includes commissioned texts by Philip Hoare and Jean Wainwright, alongside interviews with each of the artists in which they talk about their contributions to the exhibition. Exhibition: John Hansard Gallery & SeaCity Museum, Southampton, UK (08.02.-04.05.2014)
"Ship to shore: art and the lure of the sea" emerged from an exhibition held at Southampton's SeaCity Museum and John Hansard Gallery in 2014" (genaue Ausstellungsdaten ermittelt)
Keywords: Seeschifffahrt -- Motiv; Meer -- Motiv; Kunst; Sea in art / Exhibitions; Artists / Interviews; Ausstellungskatalog -- John Hansard Gallery -- 08.02.2014-04.05.2014 -- Southampton; Ausstellungskatalog -- SeaCity Museum -- 08.02.2014-04.05.2014 -- Southampton